Community Colleges and Community-Campus Partnerships - Ottenritter, Nan. ([Washington D.C.] : Distributed by ERIC Clearinghouse, 1998)
This article describes the unique role of America's community colleges and the way they relate to academic health centers and community health needs. It discusses how community colleges benefit underserved communities. As open-door institutions, they provide academic opportunities for those who would not normally be able to have higher education. Community colleges also help build needed skills and provide various psychological, health, and support services to the community. The mutual collaboration between community colleges and health professions schools could provide disadvantaged students with career exploration in health and unite health professions schools more directly with the community, while health care schools could provide primary health care and research expertise to colleges. Models of community-community college partnerships are provided, citing examples from the City College of San Francisco and Northern Virginia Community College, which, through collaboration, provide valuable health services to the community, including HIV testing and health care training opportunities for students. The article concludes with recommendations for future collaborative efforts. Contains 17 references. (YKH)
Partnership Perspectives, v1 n1 p55-62 1998.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Access to Education; Community Colleges; Community Health Services; Disadvantaged Youth; Health Education; Health Needs; Health Promotion; Job Training; Partnerships in Education; Public Health; School Community Relationship; Two Year Colleges; City College of San Francisco CA -- Northern Virginia Community College; Journal Articles; Reports, Descriptive